Kolaborasi Petani dengan Badan Usaha Milik Desa dalam Pemasaran Gula Merah di Desa Rumbai Jaya - Muammar Amar Alkadafi; Muh. Said HM; Muhammad April; Fitria Ramadhani Agusti NST (MENARA RIAU, 2020)
One of the economic potentials of the community of Rumbai Jaya Village, Kempas District, Indragiri Hilir Regency is the production of local coconut derivatives. The problem is large production, but it does not have a wider market reach. The purpose of service is to create cooperation or collaboration between farmers and village-owned enterprises in marketing brown sugar products. Service Method, the service team provides assistance in the form of facilitating farmers to institutionalize farmers to work together with the Village-Owned Enterprises in marketing brown sugar to a wider market reach. The result of dedication is the collaboration between the farmers of Village Owned Enterprises, to market brown sugar products to a wider market reach. The collaboration resulted in an agreement and commitment between the village government and the Village Owned Enterprises, to form an integrated business unit for managing coconut derivatives.